(untitled) (AYUSHDHARA, 2025)
Aacharya Sushruta have explained the use of Kriyakalpa and another Chikitsa according to Sama and Niram avastha of Netra Roga. The concept of Ama is the most important fundamental principle of Ayurveda in understanding the physiopathology of the diseases. Aamvichar has its unique significance in the Nidan and Chikitsa of disease. Sama avastha in Netraroga includes Udirna Vedana (acute pain), Rag (redness), Shotha (swelling), Nistoda (pricking sensation) etc. Whereas Nirama Netraroga lakshana include Kandu (itching), Mandvedana, Prasanna Varnata etc. Aqueous tear deficit, immune cell infiltration into the corneal stroma, loss of goblet cells in the conjunctiva, and increased cytokine levels in the tears and aqueous humour are among the changes that current research says occur in chronic inflammation of the eyes. Seka, Bidalaka and Ashchyotana are the procedures performed in Aama avastha of the disease which are advised in inflammatory process of eyes, whereas Tarpana, Putapaka and Anjana are performed in Niram Avastha of the disease and has the ability to reach the posterior segment of eye. These topical treatments have transcorneal permeation and has ability to act by both lipophilic and hydrophilic pathway. It acts by decreasing Kapha in Netra Roga thereby decreasing symptoms of Netra Roga.